IMMERSE - (:unkn) unknown (My University, 2026)
IMMERSE was founded in 2017 and has revolutionised the field of Virtual Reality language teaching and learning. Having, both, a social and educational character, one of its pillars is the concept of ‘community’. It aims at creating a sense of community among learners with common interests and learning needs who will conversate with real people in realistic immersive contexts. Moreover, IMMERSE is the first synchronous VR language teaching and learning platform, and has focused ever since on longterm linguistic interactions and not on rudimentary understanding of vocabulary and sounds. At present, it is the leading Metaverse language learning platform and it has launched a Spanish language learning programme, followed by French, English, and Japanese in the upcoming months.